Intervensi militer dan penerapan kebijakan Orde Baru di Udanawu, Kabupaten Blitar (1969-1983 an) - Amirudin, Muhammad Rifki (Historiography: Journal of Indonesian History and Education, 2024)
Abstract The Pancasila Village Project is President Soeharto's modernization program in the Blitar area. Therefore, this research aims to narrate the progress of the Pancasila Village project during the New Order era as well as the forms of implementation of President Soeharto's government policies in Udanawu District from 1969 to 1983.. This research was motivated by the emergence of one of the villages in Udanawu District as one of the areas that was successful in implementing the modernization and development program at the beginning of the New Order government. The modernization program that was preceded by the purge of communists is an interesting paradox to study. The method used in this research is a historical research method which includes topic selection, heuristics, criticism, interpretation and historiography using a social history approach carried out with interpretation from archives, newspapers, and articles. This research found that military intervention through Pancasila Village was less visible in the lives of the people of Udanawu. The term Pancasila Village is not well understood by village communities in the Udanawu District area. Even two village officials in the Udanawu District area did not know that Pancasila Village existed. However, between 1969 and 1983 the government succeeded in improving agriculture, controlling population, and building several other supporting infrastructure in the Udanawu District area.Abstrak Projek Desa Pancasila adalah program modernisasi Presiden Soeharto di wilayah Blitar. Maka dari itu, Penelitian ini bertujuan untuk menarasikan berjalannya proyek Desa Pancasila pada masa Orde Baru serta bentuk-bentuk penerapan kebijakan pemerintahan Presiden Soeharto di Kecamatan Udanawu pada tahun 1969 hingga 1983 an. Penelitian ini dilatarbelakangi oleh munculnya salah satu desa di Kecamatan Udanawu sebagai salah satu wilayah yang berhasil dalam pelaksanaan program modernisasi dan pembangunan pada awal pemerintahan Orde Baru. Program modernisasi yang didahului pembersihan orang-orang komunis menjadi paradoks menarik untuk diteliti. Metode yang digunakan dalam penelitian ini adalah metode penelitian sejarah yang meliputi pemilihan topik, heuristik, kritik, interpretasi, dan historiografi dengan menggunakan pendekatan sejarah sosial yang dilakukan dengan interpretasi dari arsip, koran, dan artikel. Penelitian ini menemukan fakta bahwa intervensi militer lewat Desa Pancasila kurang tampak dalam kehidupan masyarakat Udanawu.  Istilah Desa Pancasila kurang dimengerti keberadaannya oleh masyarakat desa di wilayah Kecamatan Udanawu. Bahkan dua pejabat desa di wilayah Kecamatan Udanawu tidak mengetahui adanya Desa Pancasila.